Strategi Layanan Konseling Kelompok Dengan Teknik Positive Reinforcement Untuk Mengurangi Perilaku Merokok Siswa SMP Negeri 2 Martapura - Akhmad Sanusi; Jarkawi Jarkawi; Akhmad Rizkhi Ridhani (JURNAL KONSELING GUSJIGANG, 2020)
The purpose of this study is to analyze the level of behavior of students smoking before and after the service, and analyze the level of effectiveness of service strategies. In this study, researchers used a pre-experimental design that is one-group pretest and posttest design. Pretest-treatment-posttest research procedure. The sampling technique uses purposive sampling. Data collection techniques using a measurement scale through the instrument. Validity and reliability using Pearson Correlation and Cronbach alpha. Analyzing, experimental results, researchers used descriptive statistical counts, and tested the effectiveness of the service test with the Wilcoxon formula with the help of the IBM SPSS Statistics 23 application. treatment 224 or 41%, the average yield can be classified as low. Level of service effectiveness Based on the results of the Wilcoxon test calculation on student data obtained that the significance value (Sig). 0.012 is less than 0.05. The influence of smoking behavior before and after the service is provided.